West Africa’s data story: The availability of actionable nutrition data - Diatta, Dieynab; Billings, Lucy; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
The past decade has seen a growing global and regional momentum to prioritize nutrition and to develop actionable programs for improved nutrition and more effective food systems. This momentum is reflected in various initiatives at the global level such as the six World Health Assembly (WHA) global nutrition targets, the 2030 Agenda, and the Sustainable Development Goals. These agendas, however, can only be achieved by a comprehensive and coherent set of actions, programs, and policies that address both the immediate and underlying causes of malnutrition. The availability of high quality, timely, and reliable data is key to the efficient monitoring and tracking of progress toward these global- and national-level targets; it supports the effective prioritization of actions and improves the ability to track implementation strategies and investments for reducing malnutrition and measuring their impact. The 2014 Global Nutrition Report promulgated the idea of a data revolution at a point when many countries did not have such data available. Since then, multiple data efforts have been undertaken, including Countdown to 2030, the formation of various technical experts groups, and the constitution of a global nutrition data partnership group